THE ROLE OF LAPAROSCOPY IN THE DIAGNOSIS AND TREATMENT OF INFERTILITY ASSOCIATED WITH THE PATHOLOGY OF UTERINE SURPLUSES IN WOMEN - Burxonova , S.B.; Solieva, Z.F.; Sharipova, Sh.O.; Gafurova, E.O. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. In the structure of female infertility, pathologies of the uterus excess occupy a leading position. The role of reproductive Surgery in the diagnosis and treatment of infertile women is incomparable. The purpose of the study is to assess the role and effectiveness of laparoscopy in the diagnosis and treatment of sterile associated with the pathology of uterine surpluses in women. Materials. The study included 100 women with pathologies over the uterus. 30 of them were women with ovarian follicular cysts (Group 1), 30 were women with occlusion of the ampular part of the fallopian tubes (Group 2), 20 were women with polycystic ovary syndrome (Group 3) and 20 were women with similar pathologies, but not performed surgery for the comparison group. All patients underwent clinical-laboratory, hormonal, ultrasound and chromotubation studies. Laparoscopic surgery "Karl Storz" was performed using endoscopic equipment. Results. During laparoscopic surgery, 80 patients were diagnosed with various pathologies of the uterus, in particular, ovarian follicular cyst in 30 patients, occlusion of the ampular part of the fallopian tubes in 30 patients, and ovarian polycystosis syndrome in 20 patients. In women diagnosed with these uterine excess pathologies, they were eliminated by laparoscopic surgery. Conclusion. The use of laparoscopy in infertile women, associated with the pathology of uterine surpluses pathologies, makes it possible to diagnose these pathologies and eliminate them surgically, after surgery, pregnancy increases in weight by 2.1 times, leads to recovery of reproductive activity in 84.3% of cases.